Hubungan Kadar Hemoglobin Glikosilat (HbA1c) dengan Kandidiasis Kutis pada Pasien Diabetes Melitus Tipe 2 di Rumah Sakit Umum Daerah Dr. Pirngadi Medan Pada tahun 2019 - Agatha, Theresia Christin; Marpaung, Okto; Sibarani, Joseph (Nommensen Journal of Medicine, 2023)
Background: Cutaneous candidiasis is a fungal infection of the skin caused by yeast or microorganisms belonging to the genus Candida. It is known that diabetes mellitus is one of the predisposing factors for candidiasis cutis caused by changes in the body's defense system. Diabetes mellitus is a metabolic disease characterized by hyperglycemia resulting from defects in insulin secretion or insulin action. Starting from the autoimmune destruction of pancreatic cells resulting in insulin deficiency to abnormalities resulting in resistance to insulin action. To determine a person's level of glucose control, an HbA1c examination is needed. This test will show the average blood sugar level over the last 90 days and represent a percentage. This test can also be used to diagnose diabetes. Objective: To analyze the relationship between HbA1c levels and cutaneous candidiasis in type 2 diabetes mellitus patients. Methods: This study is an observational analytic study with a retrospective design. To determine the relationship between glycosylated hemoglobin (HbA1c) levels and cutaneous candidiasis in type 2 diabetes mellitus patients. On examination of HbA1c levels it can be said to be controlled < 6.5% and not controlled > 6.5%. Results: The results of this study were taken from 62 patient medical record data according to the inclusion and exclusion criteria, it was found that the majority of patients with type 2 diabetes mellitus were women aged ≥55 years. Based on HbA1c levels, the patients in this study were more dominantly uncontrolled with negative cutaneous candidiasis, 56 (90.3%). The results of Fisher's exact analysis showed p-value = 1.000 (p > 0.05) meaning that there was no significant relationship between HbA1c levels and cutaneous candidiasis. Conclusion: There is no significant relationship between HbA1c levels and the incidence of cutaneous candidiasis.